2020
DOI: 10.1088/1361-6579/abb8bf
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning for nocturnal mass diagnosis of atrial fibrillation in a population at risk of sleep-disordered breathing

Abstract: Objective: In this research, we introduce a new methodology for atrial fibrillation (AF) diagnosis during sleep in a large population sample at risk of sleep-disordered breathing. Approach: The approach leverages digital biomarkers and recent advances in machine learning (ML) for mass AF diagnosis from overnight-hours of single-channel electrocardiogram (ECG) recording. Four databases, totaling n = 3088 patients and p = 26 913 h of continuous single-channel electrocardiogram raw data were used. Three of the da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…Holter ECG, single-lead ECG in PSG and in cases of implanted pacemakers. In a recent research of ours (Chocron et al 2020), we demonstrated that over 22% of individuals with undiagnosed atrial fibrillation could be identified by opportunistic data-driven nocturnal screening of the ECG traces recorded in regular PSG studies. Research has also shown that atrial fibrillation events may be more frequent during sleep than daytime (Yamashita et al 1997), but this may not be the case for other cardiac abnormalities (Portaluppi and Hermida 2007).…”
Section: Cardiac Monitoring During Sleepmentioning
confidence: 92%
“…Holter ECG, single-lead ECG in PSG and in cases of implanted pacemakers. In a recent research of ours (Chocron et al 2020), we demonstrated that over 22% of individuals with undiagnosed atrial fibrillation could be identified by opportunistic data-driven nocturnal screening of the ECG traces recorded in regular PSG studies. Research has also shown that atrial fibrillation events may be more frequent during sleep than daytime (Yamashita et al 1997), but this may not be the case for other cardiac abnormalities (Portaluppi and Hermida 2007).…”
Section: Cardiac Monitoring During Sleepmentioning
confidence: 92%
“…Transient desaturations (even to 70% or less) are commonly observed in infants with bronchiolitis after discharge, but their clinical significance remains unclear 28 In clinical practice, there are a few instances where nocturnal ECG is recorded, e.g., Holter ECG, single-lead ECG in polysomnography (PSG) and in cases of implanted pacemakers. In a recent research of ours 33 , we demonstrated that over 22% of individuals with undiagnosed atrial fibrillation could be identified by opportunistic data-driven nocturnal screening of the ECG traces recorded in regular PSG studies. Research has also shown that atrial fibrillation events may be more frequent during sleep than daytime 34 , but this may not be case for other cardiac abnormalities 35 .…”
Section: Ventilation During Sleepmentioning
confidence: 92%
“…Broadening our knowledge of pathophysiological patterns during sleep may enable harnessing of machine learning algorithms to support screening strategies in selected populations. For example, opportunistic nocturnal screening for hypertension, atrial fibrillation 33 or COPD 27 , may be performed in high risk patient populations.…”
Section: Cancer Therapymentioning
confidence: 99%
“…For SHHS, the ECG peaks were detected using epltd0 [46] a state-of-the-art ECG peak detection algorithm. PRV and HRV measures were extracted using the Python HRV features implemented in [47]. This library calculates 21 HRV measures per set of IBIs.…”
Section: Feature Engineeringmentioning
confidence: 99%